Electrical and mechanical properties of PZT/PVDF 0-3 composites - Thongsanitgarn P. (2014)
Granules of in-house prepared PZT ceramic and powder of commercially available PVDF polymer were used as starting materials to form a series of xPZT/(1 - x)PVDF composites (where x = 0, 0.1, 0.3, 0.5, 0.7, 0.9, and 1.0) with 03 connectivity. Densities of the composites tended to increase with increasing PZT ceramic content. Phase and microstructure of the composites revealed homogeneous mixture between PZT and PVDF phases. The composites with higher ceramic content had higher dielectric constant and dielectric loss tangent. Ferroelectric measurement revealed the effect of PZT phase connectivity in 0.9PZT/0.1PVDF ceramic in which a sudden jump in ferroelectric properties was observed. Mechanical properties in terms of hardness, Young's modulus and fracture toughness were also improved when PZT content was increased. © 2010 World Scientific Publishing Company.